The effect of front squats on the net ability of junior weightlifters - Nazwa Shalsabilla; Cut Vidya Aslina; Bagas Aryo Prayogo; Reksy Dwiyulian Putra; Ely Yuliawan; Wawan Junresti Daya (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problem: Athletes sometimes have trouble performing the final position of the Clean, this error generally occurs when standing to complete the Clean. This happens due to the lack of strength of the main muscles involved in the Clean technique, observed directly when athletes perform the Clean Exercise program, among which there are those who do not succeed in doing the final position of Clean, that is, standing perfectly with the barbell position still on the shoulder. Therefore, to overcome these problems, supportive exercises are carried out to strengthen the main muscles involved in the clean technique, namely the Front Squat. Objective: To prove that the Front Squat exercise has an effect on the improvement of the main muscles that play a role in Clean. Methods: This research method is a Quantitative Experimental research with a Paired Sample T test research design. The instruments used are Pre-test and Post-test. Using the Jamovi statistical test. Results: The results of the paired sample t-test showed a significant increase in score from pre-test to post-test, t(11) = -10.70, p < 0.001. The mean score difference was -3.08 (SE = 0.288) with a 95% confidence interval between -3.72 to -2.45. A measure of the Cohen effect d of −3.10 suggests that the intervention has a very large effect. Conclusion: Based on the results of a study that has been conducted for four weeks by providing Front Squat gymnastics twice every week, it can be concluded that Front Squat exercises have a significant influence on the improvement of Clean ability in Jambi City Junior Weightlifters in Jambi City. The results of the t-test analysis of paired samples showed a significant increase between pre-test and post-test values, t(11) = -10.70, p < 0.001, with an average score difference of −3.08. The enormous effect size (Cohen's d = −3.10) confirms that the Front Squat has a strong impact on improving the strength and performance of the Clean technique